2022
DOI: 10.1002/ctm2.1048
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic interleukin‐1 receptor type 1 signalling regulates insulin sensitivity in the early phases of nonalcoholic fatty liver disease

Abstract: Background Nonalcoholic fatty liver disease (NAFLD) is associated with hepatic as well as systemic insulin resistance even in the absence of type 2 diabetes. The extent and pathways through which hepatic inflammation modulates insulin sensitivity in NAFLD are only partially understood. We explored the contribution of hepatic interleukin (IL)‐1 signalling in a novel conditional knockout mouse model and expand the knowledge on this signalling pathway with regard to its liver‐specific functions. Methods A high‐fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…The IL1 pathway, especially IL1B, has attracted significant attention and has been extensively researched within the realm of NAFLD (35,(44)(45)(46)(47). IL-1β exacerbates liver steatosis, inflammation, and fibrosis by interacting with the IL-1 receptor, which is extensively expressed across various liver cell types (44).…”
Section: Discussionmentioning
confidence: 99%
“…The IL1 pathway, especially IL1B, has attracted significant attention and has been extensively researched within the realm of NAFLD (35,(44)(45)(46)(47). IL-1β exacerbates liver steatosis, inflammation, and fibrosis by interacting with the IL-1 receptor, which is extensively expressed across various liver cell types (44).…”
Section: Discussionmentioning
confidence: 99%
“…It underscored the contribution of hepatocyte IL-1R1 to (extra)hepatic insulin resistance. It suggested that treatment for NAFLD, by improving hepatic inflammation and IL-1R1 signaling, could have beneficial effects on insulin sensitivity [ 15 ].…”
Section: Pathophysiological Aspects Of Interleukins In Nafldmentioning
confidence: 99%
“…Generally, short-term high-fat feeding leads to the development of steatosis but not steatohepatitis, especially in the absence of inflammatory signals, whereas long-term high-fat feeding can lead to NASH [54]. Multiple lines of study highlight the role of IL-1 signaling in the progression of hepatic steatosis, suggesting a crucial role for inflammasome activation in the subsequent process [55,56]. IL-1β can promote insulin resistance, leading to a disruption in the insulin-mediated regulation of lipogenesis, which can result in the accumulation of fat in the liver [57].…”
Section: High-fat Diet-induced Hepatotoxicitymentioning
confidence: 99%